2017
DOI: 10.1128/jb.00393-16
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor Mutations LinkinggpsBwith the First Committed Step of Peptidoglycan Biosynthesis in Listeria monocytogenes

Abstract: The cell division protein GpsB is a regulator of the penicillin binding protein A1 (PBP A1) in the Gram-positive human pathogen Listeria monocytogenes. Penicillin binding proteins mediate the last two steps of peptidoglycan biosynthesis as they polymerize and cross-link peptidoglycan strands, the main components of the bacterial cell wall. It is not known what other processes are controlled by GpsB. L. monocytogenes gpsB mutants are unable to grow at 42°C, but we observed that spontaneous suppressors correctin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
103
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(114 citation statements)
references
References 41 publications
11
103
0
Order By: Relevance
“…Inactivation of clpC (encoding an ATPase subunit of the proteasome), of murZ (encoding an UDP‐GlcNAc 1‐carboxyvinyltransferase) and of genes encoding other UDP‐GlcNAc consuming enzymes (GtcA, Lmo2550) also suppress the phenotype of the Δ gpsB mutant, at least its growth defect at higher temperature (Rismondo et al ., ). It has been assumed that these suppressor mutations compensate the effects of PBP A1 inefficiency by redirection of additional precursor molecules into the peptidoglycan biosynthetic pathway (Rismondo et al ., ). We measured the effect of two such suppressor mutations ( clpCR254S and murZ 1–253 ) on lysozyme resistance of the Δ gpsB mutant and found that resistance against lysozyme is corrected back to wild type level in these strains (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Inactivation of clpC (encoding an ATPase subunit of the proteasome), of murZ (encoding an UDP‐GlcNAc 1‐carboxyvinyltransferase) and of genes encoding other UDP‐GlcNAc consuming enzymes (GtcA, Lmo2550) also suppress the phenotype of the Δ gpsB mutant, at least its growth defect at higher temperature (Rismondo et al ., ). It has been assumed that these suppressor mutations compensate the effects of PBP A1 inefficiency by redirection of additional precursor molecules into the peptidoglycan biosynthetic pathway (Rismondo et al ., ). We measured the effect of two such suppressor mutations ( clpCR254S and murZ 1–253 ) on lysozyme resistance of the Δ gpsB mutant and found that resistance against lysozyme is corrected back to wild type level in these strains (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 97%
“…S7). It has been shown that MurA, which is the primary UDP‐GlcNAc 1‐carboxyvinyltransferase of L. monocytogenes and catalyzes the first committed step of peptidoglycan biosynthesis, is approximately tenfold overproduced in these suppressor strains, leading to redirection of precursors into cell wall biosynthesis (Rismondo et al ., ). In contrast, pbpA1 inactivation does not affect the MurA protein level at all (Rismondo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Genomic DNA was isolated using the GenElute™ Bacterial Genomic DNA Kit (Sigma-Aldrich) as described (Halbedel et al, 2018). Libraries were prepared using the Nextera XT DNA Library Prep Kit and genomes were sequenced on a MiSeq benchtop sequencer as described recently (Rismondo et al, 2017). SNPs were identified using the Geneious software package and the EGD-e genome sequence (NC_003210.1) (Glaser et al, 2001) as the reference.…”
Section: Genome Sequencingmentioning
confidence: 99%
“…Other than the capsular biosynthetic operon that is absent in R6, other directly relevant genotype differences include: dltA , which is responsible for the d ‐alanylation of teichoic acids; murA1 , which catalyses the first step in PG biosynthesis; ftsX , an ABC transporter‐like integral membrane protein essential for normal cell division; pbp1A , a bifunctional PBP and cbpD , a PG hydrolase (Lanie et al ., ). It is perhaps pertinent to note that growth of L. monocytogenes gpsb null strains can be suppressed by spontaneous mutation in murZ , a listerial paralogue to murA (Rismondo et al ., ). Since the R800 strain is a cousin of R6 (Fleurie et al ., ) it is entirely plausible that these genetic differences, and/or some unknown suppressors in R800, could explain the GpsB and DivIVA phenotypic differences between S. pneumoniae strains used in labs around the world.…”
Section: Suppressor Accumulation and Genetic Variability Between Strainsmentioning
confidence: 99%